DEVELOPING A MODEL TO INVOLVE SERVICE USERS IN A MULTI-CENTRED TRIAL OF A COMPLEX INTERVENTION IN PRE-HOSPITAL EMERGENCY CARE. Issue 5 (18th April 2015) - Koniotou, M; Halter, M; Evans, B A; Porter, A; Gaze, S; ,
Abstract : Background: Research collaborations with patient and professional groups can ensure health research funders are aware of what matters to patients, carers and clinicians. Increasing service user involvement in research improves research quality, accountability and provision of patient-centred services. There is little evidence about involving service users in trials or pre-hospital emergency care research. Most research involving service users concerns a condition or treatment rather than service delivery or point of entry to the healthcare system. The SAFER 2 trial evaluates a complex intervention enabling paramedics to assess older people who fall and call 999 and, where appropriate, refer them to a community care pathway. Objective: To describe a model for involving service users in a multi-centred trial in emergency care. Method: A Standard Operating Procedure (SOP) for including service users was developed by the clinical trials unit West Wales Organisation for Rigorous Trials in Health (WWORTH). This recommends involvement processes and supportive working practices, based on evidence and good practice. We adapted this SOP to develop a model to involve service users in our trial of a complex intervention in pre-hospital care. Results: We included service users at three different decision levels of involvement: Strategic level: Data Monitoring and Ethics Committee, Trial Steering Committee, Trial Management Group and Trial Development Group. These are the standard bodies that manage and oversee the trial. Local level: management committees. These take decisions about running the trial in each study site. Service user reference groups: these groups of patients and carers meet with the site researcher to discuss issues affecting patients likely to be recruited into the study. Conclusion: The principles and processes of the SOP provided a model that could be replicated across each trial site. We found it necessary to tailor and adapt.